MEDIA BUSINESS STRATEGY : CASE STUDY OF PALOPO POS NEWSPAPER - Muhammad Fadhli Febrian Amir; Abdul Rahman Kadir; Sumardi Lasise (Hasanuddin Journal of Applied Business and Entrepreneurship, 2022)
One of the major industries that have undergone a major transformation in the media industry. The influence of technology makes this industry more dynamic. Empirical facts from the impact of digitizing the media industry have been felt by several media that previously dominated the media market This research will analyze the success of the Palopo Pos newspaper as one of the media that is able to survive and exist to this day, both in terms of business and in terms of content or rubric. To analyze the success of the strategy carried out by the Palopo Pos newspaper, it is based on structure, performance, and conduct with other economic theories. The number of readers, company efficiency to the number of advertisers are indicators used to measure and analyze the success of the Palopo Pos newspaper.